Prevalence of Distant Metastases in Whole-Body Scan after Iodine Therapy in Low- and Intermediate-Risk Differentiated Thyroid Cancers - A Gholami; A Alipour; H Gholinia; SH Mousavie Anijdan (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Differentiated Thyroid Cancer (DTC) is the most common endocrine malignancy with the fastest growing rate worldwide. The aim of this study is to investigate the prevalence of distant metastases in whole-body scans after iodine therapy in DTC patients with low and intermediate-risk and to evaluate its diagnostic role. Methods: In this retrospective cohort study, patients with DTC who underwent total thyroidectomy and were referred for Radioiodine Remnant Ablation (RRA) to the nuclear medicine department of Shahid Beheshti Hospital were included in the study. According to ATA guidelines, patients were divided into two groups with low risk level (LR) and intermediate risk level (IR) and were evaluated for distant metastasis by whole-body scan after iodine treatment with a Single-Head Gamma Camera. Findings: Out of 1039 patients included in the study, 149 (14.3%) were men and 890 (85.7%) were women. Thyroid remnant was present in whole-body scan after iodine treatment in 1030 patients (99.1%). Of these patients, 713 (68.6%) were in the LR group and 326 (31.4%) were in the IR group. The presence of cervical lymph node metastasis was detected in 69 people (LR:28, IR:41), mediastinal involvement in 11 people (LR:3, IR:8), lung metastases in 11 people, and bone metastasis in 3 people out of 101 patients. All of them were in the group of patients with intermediate risk. Multiorgan involvement was seen in 7 of 101 patients (LR:2, IR:5). The mean serum level of thyroglobulin (Tg) in cases of distant metastasis was 2.61±8.57 in the low risk group and 17.45±65.21 in the intermediate risk group, and these values showed statistically significant differences (p<0.001). Conclusion: The results of the present study showed that the prevalence of distant metastases in whole-body scan after iodine therapy was seen in approximately 10% of patients. Serum thyroglobulin level can also be used as a clinical marker for early diagnosis of distant metastasis.